Tutorial on combustible dust. Issue 3 (29th April 2013) - Myers, Timothy J.; Ibarreta, Alfonso F.
<x xml:space="preserve">Abstract</x> This article provides an overview of combustible dust. A summary of recent combustible dust incidents and the variety of types of materials that can represent a combustible dust hazard when present in a particulate form are provided. Fundamentals of combustible dust are covered, comparing and contrasting combustible dust to flammable gases and vapors. Test methods used to characterize the hazards of combustible dust are reviewed. Relevant standards and regulations are described. Finally, guidance on the primary methods to prevent and mitigate combustible dust incidents is summarized. © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 298–306, 2013